Consequences of Agricultural Enterprises Reorganization into Closed Joint Stock Companies During the Initial Period of Land Reform: Some Issues of Judicial Practice - E. A. Konyukh (Сибирское юридическое обозрение, 2012)
Considering some cases of judicial practice the author analyses the consequences of reorganization the former state farms and collective farms into closed joint stock companies during the initial period of land reform. It is connected with these newborn agricultural enterprises entitlement registration into common land plot of agricultural use.